Patients' experiences of sexuality as a taboo subject in the Danish healthcare system: a qualitative interview study. Issue 1 (15th October 2018) - Traumer, Line; Jacobsen, Michael Hviid; Laursen, Birgitte Schantz
Abstract : Background: Sexual dysfunction is common in patients diagnosed with cancer or chronic disease, having psychological, emotional and social ramifications. The consequences are ultimately significant impaired quality of life and reduced mental well‐being, and it therefore requires professional attention. However, evidence suggests that sexuality is a taboo subject in the healthcare system, as healthcare professionals and patients rarely initiate conversations on this subject. Aim: Therefore, the purpose of this study was to understand how patients diagnosed with cancer or chronic disease experiencing sexual dysfunction experience sexuality as a taboo subject in the healthcare system. Methods: Ten women diagnosed with cancer or chronic disease experiencing sexual dysfunction were recruited from the Sexological Centre in Aalborg, Denmark. Using an interview guide, semi‐structured interviews were conducted and a qualitative thematic analysis was performed. Results: The analysis revealed that sexuality is a sensitive and taboo subject in the Danish healthcare system. Some patients initiated conversations about their sexuality, but felt rejected by healthcare professionals, who dismissed these initiatives, whereas other patients were reluctant to discuss sexuality, but did not experience healthcare professionals bringing up sexuality either. Despite these differences between patients' experiences, sexuality constituted a taboo subject, as patients or healthcare professionals deliberately avoided discussing the patients' sexuality‐related issues. Conclusions: Communication about sexuality is essential for improving patients' well‐being, and healthcare professionals should routinely address sexuality and sexual intimacy with patients diagnosed with cancer or chronic disease in order to break the taboo and accommodate patients' needs.